Base of tongue tuberculosis: a case report - Hussaini, J.; Mutusamy, S.; Omar, R.; Rajagopalan, R.; Narayanan, P. (2012)
We report a rare case of base of tongue tuberculosis following pulmonary tuberculosis. Patient presented to us with chief complaints of sore throat and pain on swallowing for period of 3 months. On examination with 70 degree telescope, we observed an ulcer on right side of base of tongue. The edges of the ulcer appeared to be undermined with whitish slough at the centre of the ulcer. Examination of neck showed a multiple small palpable middle deep cervical lymph nodes on right side of neck. Biopsy of the ulcer was taken, which showed granulomatous inflammation, suggestive of tuberculosis. Laboratory investigations revealed a raise in erythrocyte sedimentation rate, sputum for acid fast bacilli was strongly positive. Chest X ray was performed for patient showed multiple areas of consolidation. Patient was referred to chest clinic for further management of tuberculosis and was started on anti-tuberculous drugs. In conclusion tuberculosis of oral cavity is rare, but should be considered among one of the differential diagnosis of the oral lesions and biopsy is necessary to confirm the diagnosis.